The Impact of the Implementation of Stock Index Options on Stock Market Volatility: China Evidence - Xiao, Shixin (2019)
The stock market can be a leading indicator of a country's economic performance. In real life, the stock market is full of volatility and uncertainty. The emergence of stock index options enriches the financial market and expands the opportunities for investors. The effect of stock index options on stock market volatility has always been an interesting topic for financial researchers. This paper chooses to study the Chinese stock market and chooses the SSE 50 index as the main research object. By excluding the influence of domestic and international economic situation, this paper analyses the impact of the implementation of SSE 50 ETF option on the volatility of Chinese stock market and puts forward some suggestions according to the current situation.